DETERMINANTS OF PRIVATE INVESTMENT IN LESOTHO - Molapo, Senei; Damane, Moeti (European Scientific Journal, ESJ, 2015)
The study empirically examines the determinants of private investment in Lesotho over the period 1982 – 2013. The results indicate that private investment is positively influenced by the level of economic growth and public investment while it is negatively affected by increase in the price level. The highly significant and positive coefficient of economic growth confirms the accelerator principle in Lesotho while that of public investment outlines the significant role of government in laying down infrastructure to crowd in private investment. The negative coefficient of the general price level symbolizes the importance of price stability in stimulating private investment. In addition, the study confirms that macroeconomic instability negatively affects private investment in Lesotho. The Granger-Causality test reveals that there is unidirectional causality running from private investment to per capita GDP, and bidirectional causality between public and private investment. The policy recommendation following the findings is that government should engage in investment of infrastructural projects in the short-run to better aid smooth private investment in the long-run.